Implementation of Pillar I and Pillar III Community-Led Total Sanitation (CLTS) in Reducing the Incident of Stunting in Pangkep District - Sahani, Wahyuni; Inayah, Inayah; Syamsuddin, Syamsuddin (Jurnal Kesehatan Masyarakat, 2025)
Community-Led Total Sanitation (CLTS) is an approach to changing hygiene and sanitation behavior through community empowerment activities by triggering. The purpose of this study was to determine the application of pillars 1 and 3 of CLTS in reducing the incidence of stunting in the Pangkep Regency. The research method used an observational study with a cross-sectional approach. The study was conducted in 2023 and the population of this study were all heads of families in the subdistrict that have stunting incidence in Pangkep Regency. Sampling using accidental sampling technique was taken in Taraweang Village, Labakkang District as many as 63 heads of families, and in Buwong Cindea Village, Bungoro District as many as 78 heads of families. The research instrument used a questionnaire based on the guidelines of the Ministry of Health of the Republic of Indonesia. The results showed that there was a relationship between the implementation of Pillar 1 and Pillar 3 of Community-Led Total Sanitation (CLTS) in reducing the incidence of stunting in Taraweang Village, Labakkang District, and Buwong Cindea Village, Bungoro District, Pangkep Regency with the results of statistical tests obtained at (0.05 < 0.05) and (0.002 < 0.05). It is necessary to implement CLTS comprehensively so that the results of public health achievements can be maximized and the incidence of stunting can be prevented.